Does Consumption of Coloring Substances during Tooth Whitening Treatment Influence the Final Outcome? A Systematic Review - Soares, Marilia de Lima; Carvalho, Marianne de Vasconcelos; Lemos, Cleidiel Aparecido Araújo; Souto Maior, Juliana Raposo; Moraes, Sandra Lúcia Dantas de; Vasconcelos, Belmiro Cavalcanti do Egito; Rosa, Cleber Davi Del Rei Daltro; Pellizzer, Eduardo Piza (ARCHIVES OF HEALTH INVESTIGATION, 2021)
The purpose of this systematic review recorded in PROSPERO (CRD4201913125) was to test the hypothesis that dye substances during and / or immediately after treatment can affect the effectiveness of tooth whitening. Two independent reviewers performed a search was conducted in the PubMed / MEDLINE, Web of Science databases and Cochrane Library. Articles were selected based on the inclusion criteria: in vitro studies with direct comparisons between groups undergoing treatment with or without dying substances consumption during or immediately after bleaching treatment; reflectance spectrophotometry was used as evaluation method; studies in which any type of dye was used, studies in which treatment was performed on human and / or bovine teeth. Of the 8 studies selected, including 347 samples analyzed in vitro. The coffee does not appear to influence tooth whitening when consumed during tooth whitening sessions or immediately after treatment (up to 24 hours after treatment). However low-alcoholic beverages such as red wine and cola drinks may have the potential to change pigmentation and influence the change in tooth color.